BASIC EDUCATION POLICY PERSPECTIVE CHARACTERISTICS OF LEARNERS - Mizaniya Mizaniya (Sunan Kalijaga International Journal on Islamic Educational Research, 2020)
Education policy is a public policy in the field of education. In the national policy, among others, it is emphasized that the development of the nation's character is a fundamental need in the process of nationhood and statehood. Sometimes students in learning activities do these three learning styles. The research method used is a literature research method whose research object is searched through a variety of literature information (books, scientific journals, newspapers, magazines, documents) and so on with data analysis techniques. Each implementation of education has been regulated based on policies including the implementation of character education. the formation of the character and moral education of learners so that it becomes the next generation of the nation that has a strong foundation of both knowledge, skills, religion, and national values. Therefore, learning activities, classroom organization, learning materials, learning time, learning tools, and assessment methods need to be adjusted to the characteristics of the students. Of all the characteristics possessed by the above students, it is necessary to be noticed by an educator. So an educator must be able to understand every character that the students have so that the learning process can take place smoothly, effectively and efficiently. So that the educational goals that have been envisioned can be achieved.